Factor Related to Herbal Use Behavior for Self-care among People in Phasi-Chareon District - Deenoo, Sutida; Mattavangkul, Chanida; Kawitu, Kwanruen; Sinwannakool, Sirinat (Journal of Nursing, Siam University, 2020)
The survey research aimed to understanding the behavior of using natural herb for curing themselves. The data was collected by questionnaires – validated by related subject to find out the relation among 1) leading factors (sex, age, education, profession, income, disease), 2) Facilitating factor (Knowledge, attitudes, determined) and 3) additional factor (choice, expenditures). The sample size was 140 samples which were randomized from proportion population of each seven sub-districts. The data was analyzed by using frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient and Chi-square test for correlation. The result were revealed that the positive correlation with behavior of natural herbs to take care of themselves among personal factors including age, income, and underlying disease at 0.05 level of statistical significantly. The research recommended promoting and enhancing to more and correctly using natural herbs for people of Phasi-Charoen, which is suitable in context of Bangkok.